EVALUASI KINERJA GURU IPA SD, SMP, DAN SMA PASCA SERTIFIKASI - Suparwoto Suparwoto (Jurnal Kependidikan, 2011)
The study is aimed at describing teachers perceptions of their competencies after their certification processes in relation to their work performances in elementary schools, junior secondary schools, and senior secondary schools. The study is evaluation research as a follow-up of the certification process. The participants are Physics teachers of elementary schools, junior secondary schools, and senior secondary schools in Yogyakarta. The study involves two research stages of preliminary and development activities. The preliminary stage consists in reference reviews and field work to obtain accurate information on the research problems. The development stage consists in the contruction and validation of the research instruments. The validated instrument is used for data collection. Findings show that the most prominent aspect of professional competencies occurs in junior secondary school teachers followed by elementary school teachers and junior secondary school teachers. The pedagogic, personal, and social aspects are prominent with elementary school teachers followed by junior secondary school teachers and junior secondary school teachers. All aspects related to work performances in all teachers show prominence in procedural matters. Creativity development is not prominent in all teachers